Households in HIV Care: Designing an Intervention to Stimulate HIV Competency in Households in South Africa - Masquillier, Caroline; Wouters, Edwin; Campbell, Linda; Delport, Anton; Sematlane, Neo; Dube, Lorraine Tanyaradzwa; Knight, Lucia (Frontiers in Public Health, 2020)
Despite the Universal Test and Treat program and widespread antiretroviral treatment rollout, South Africa is still facing HIV prevention and treatment challenges, which are aggravated by human resource shortages in the healthcare sector. Individual- and community-level responses to these HIV-related challenges are increasingly being explored, for example, in community and home-based care. The role of the household as a crucial mediating social level has, however, largely been omitted. This paper outlines the design of an intervention to stimulate the involvement of the household in support for people living with HIV in South Africa. The 6SQuID model guided the intervention development process in four phases: (1) formative research, theory formulation, and a review of the existing literature, (2) integration of the results from the formative research into the “Positive Communication Process” (P2CP model) as a mechanism of change, (3) design of a community-health-worker-led intervention as the way to deliver the change mechanism, and (4) testing and revision of the developed intervention material—called Sinako—in a small-scale pilot study. The Sinako intervention anticipates that the future of chronic HIV care in resource-constrained settings will need to integrate the patient's household into the fight against HIV.